1995
DOI: 10.1590/s0103-90161995000100002
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de variedades de arroz de sequeiro em diferentes populações de plantas, com e sem irrigação suplementar

Abstract: RESUMO: -Visando determinar os efeitos do espaçamento entre linhas (30, 40 e 50 cm) e da densidade de semeadura (50, 100 e 150 sementes/m 2 ) sobre o rendimento de grãos e algumas características biométricas de duas variedades de arroz (Oryza sativa L.), com e sem irrigação suplementar, foram conduzidos quatro experimentos em solo de cerrado, sendo dois com a variedade Araguaia e os outros com a 'Guarani'. A irrigação propiciou incremento de 90 e 35% no rendimento de grãos das v. Araguaia e Guarani, respectiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
4
0
3
Order By: Relevance
“…Furthermore, the analysis of growth rates showed higher dry matter accumulation of the whole plant, leaves, stems and pods and higher LAI when soybean was grown on these mulches, which is the likely cause of these higher grain yields, corroborating information from other authors (Santos & Costa, 1997;Antoniazzi & Deschamps, 2006;Campos et al, 2008).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the analysis of growth rates showed higher dry matter accumulation of the whole plant, leaves, stems and pods and higher LAI when soybean was grown on these mulches, which is the likely cause of these higher grain yields, corroborating information from other authors (Santos & Costa, 1997;Antoniazzi & Deschamps, 2006;Campos et al, 2008).…”
Section: Resultssupporting
confidence: 87%
“…The growth analysis can be used in the observations of physiological variables that are positively correlated with grain yield (Santos & Costa, 1997;Campos et al, 2008), providing information that help monitor the adaptation of the crop to new environments, the interspecific competition, the effects of management systems, as well as productive potential of different cultivars (Antoniazzi & Deschamps, 2006;Falqueto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ceres, Viçosa, v. 64, n.2, p. 122-131, mar/abr, 2017 produtividade de grãos de arroz, o que permite o fornecimento de elevada quantidade de fotoassimilados por um período maior (Santos & Costa, 1997;Costa et al, 2000;Falqueto et al, 2009). A produtividade das culturas é correlacionada positivamente com os índices fisiológicos.…”
Section: Resultsunclassified
“…Em condições tropicais, Costa et al (2000) verificaram que a produtividade de grãos do arroz irrigado foi correlacionada com os índices fisiológicos, apresentando os mais altos coeficientes de determinação com o crescimento radicular e a DAF. No sistema de cultivo de terras altas, as correlações entre a DAF e a produtividade de grãos do cultivar Guarani foram positivas, independentemente do emprego de irrigação suplementar (Santos & Costa, 1997).…”
Section: Resultsunclassified
“…Although there was a negative impact in plant population, the crop yield did not differ in plots with varying seed infection levels. Studies have shown that rice crops are not too sensitive to planting density with regard to yield in both irrigated rice in southern Brazil (Sousa et al 1995;Mariot et al 2003;Carmona et al 2008) and upland rice (Santos and Costa 1995;Santos et al 2002). Rice plants are able to tiller and compensate the number of panicles per area to the point of equating final kernel yield (Miller et al 1991).…”
Section: Discussionmentioning
confidence: 99%